Food provision of soldiers from roman legions to the modern armieswith special regard to the meat type meals - Kovács, Alfréd (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
In the course of history the health and good condition of soldiers in the armies are fluently proved to be at least so important terms, as the armament, or the modernization and efficiency of ammunition. The maintenance of mobility and ability of fast reaction and high fighting value and disciplined keenness of regiments and subunits claims a considerable organization. A great difference is in comparison with previous situation that physical condition and enthusiasm of the military men were decisive important in point of view for outcomes of battles and wars. Nowadays the armaments and other new battle instruments modified dramatically the role of soldiers. Today among the basic food materials the bread and meat and tha healthy drinking water have also a priority. Recently the obtaining and transport and slaughtering moreover the preparation of slaughtered animals take also about 1/3 from total organizing activity in an army. Spectacular development seems in the processing and furnishing of foods /centralized cooking and roasting and distribution/ and to reduce the weight and to exchange the content of meal packs. Till in a Roman legion a legionary soldier carried always 7-9 kgs food and drinking water on, untill the weight of an actually useful meal pack takes just about 1kg.